Podemos destacar en los estudios sin importar el estilo con el que aprendemos - Quispe Andía, Noemí Janet (2020)
This research, carried out on a sample of 101 students from the Faculty of Education (Elementary Level) of the National University of San Marcos, concluded that both high and low achieving students could have the same learning style (active, reflective, pragmatic or theoretical). Actually, “standing out as a student” would depend on some other factors, such as study habits and techniques. The academic performance of the sample was homogeneous and negative asymmetric, thus indicating that the trend is towards high performance. Being homogeneous could explain why no significant relationships were found between academic performance and learning styles, taking into account the low covariance.